Emily Dickinson in the Work of Polish Translators. Continuation of Research - Krzysztofik, Małgorzata; Wzorek, Anna (Respectus Philologicus, 2022)
This article deals with the Polish translation of Emily Dickinson’s poetry and correspondence. It is a continuation of the reflection in The Emily Dickinson Journal’s pages, which started in 2022. This time we present translations of Kazimiera Iłłakowiczówna, Andrzej Szuba, Krystyna Lenkowska, Ryszard Mierzejewski, Tadeusz Sławek, Teresa Pelka, Artur Międzyrzecki, Lilla Latus, Agnieszka Osiecka, Agnieszka Kreczmar and Ewa Kuryluk. We discuss a selection of Dickinson’s letters translated by Danuta Piestrzyńska. We emphasize the characteristic features of each of the discussed translations. Although Iłłakowiczówna discovered Dickinson for Polish readers, her translations are perceived as archaic. Szuba mainly translates aphoristic texts. Lenkowska makes an effort to be faithful to the original. The newest translators introduce Poles to unknown poems and make new translations of the texts previously rendered into Polish.
Keywords: Emily Dickinson; poetry; translation; Polish language